Dump the Dump! - Weber, Alizee. (Tufts University. Tisch Library., 2015)
Tisch Library Undergraduate Research Award Winner, 2015. This project investigates the effect on the environment and the local communities of the renovation of the 91st Street Marine Transfer Station (MTS) in the residential areas of the Upper East Side, Yorkville, and East Harlem in the City of New York. The goal of this paper is to gain an understanding of the complex concepts and challenges that underlie this burning issue to evaluate potential solutions. To do so, the discussion focuses on topics such as environmental justice and discrimination, zoning laws, pollution and industrial hazards, waste responsibility, waste reduction and recycling, and clean energy. While this paper addresses the concerns of nonprofit organizations, it strives to maintain an objective point of view on the subject at hand by contrasting those views with that of government officials, and urban and environmental planning scholars.